PENGGUNAAN MEDIA TEKS CERITA DALAM MENINGKATKAN KETERAMPILAN BERBICARA BAHASA ARAB SISWA JENJANG PENDIDIKAN DASAR - Br. Sembiring, Tria Annes; Lubis, Lahmuddin (Inspiratif Pendidikan, 2023)
Students’ Arabic speaking skills are a problem based on this research, in Arabic speaking skills a must be mastered by class VIII B students of MTs Tadib Al-Syakirin, with the mediation of story text media to improve students’ Arabic speaking skills. With that the authors conducted this study aimed at describing or describing the improvement of the Arabic speaking skills of class VIII B MTs students through the medium of story text. The researcher conducted the research in two cycles, with that the researcher used the CAR (Classroom Action Research) method by collecting test and non-test data, while the data collection technique by the test was in the form of student learning outcomes sheets, and the data collection technique by non-test was in the form of interviews, observation, and documentation. The research object was class VIII B students in the even semester of 2022-2023, a total of 17 students. In using story text media the researcher obtained results in the first cycle students achieved an average value of 56.87% which this value included in the sufficient category with that the researcher carried out cycle II with the aim of achieving completeness of student scores, cycle II achievers with an average value 82.69% belong to the very good category, the increase achieved by students by using story text media is 25.65%. So through the medium of story text with the material المَدرَسَةُ it can be seen that students’ Arabic speaking skills have increased.